1980
DOI: 10.2118/7609-pa
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Very Low Interfacial Tensions on Relative Permeability

Abstract: Laboratory studies have been conducted to determine the influence of the composition of gas and oil phases on the parameters involved in the description of two-phase flow in porous media when the compositions of the phases vary over a wide range. Relative permeabilities to gas and oil were determined under high pressure and temperature for binary systems (methane/n-heptane, methane/n-decane, etc.), leading to very wide variations of the interfacial tensions values. Investigations were focused specifically on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(43 citation statements)
references
References 12 publications
5
36
1
Order By: Relevance
“…This differs from previously published tests with model fluids, which were conducted with single-pass flow systems (Nagarajan et al 2004;Kamath 2007), in which the phases may not be in equilibrium as they enter the rock. We found that model fluids are very sensitive to mass transfer and entrapment effects.…”
Section: Ovencontrasting
confidence: 82%
See 1 more Smart Citation
“…This differs from previously published tests with model fluids, which were conducted with single-pass flow systems (Nagarajan et al 2004;Kamath 2007), in which the phases may not be in equilibrium as they enter the rock. We found that model fluids are very sensitive to mass transfer and entrapment effects.…”
Section: Ovencontrasting
confidence: 82%
“…2 shows a schematic of the reservoir-condition apparatus. The system is similar to that described by Nagarajan et al (2004) with a few major upgrades. The system is simpler and more precise in measurement because of the state-of-the-art gas-condensate recirculating system.…”
Section: Relative Permeability Measurement Methodsmentioning
confidence: 99%
“…Lefebvre du Prey [14] reported that the Kr value increases considerably for both the wetting phases in an oil-wet media. The relative permeability variation with Nc was also supported by other researchers like Bardon and Longeron [15], Amaefule and Handy [16], and Harbert [17] which confirms that Kr is a function of IFT, flow rate, absolute permeability and the fluids viscosity. On the other hand, the results of a series of steady state core flooding experiments by Fulcher et al [18] in water-wet sand stone rocks indicated that the water relative permeability was increased by Nc, however, the trend was not clear for the oil phase.…”
Section: Introductionsupporting
confidence: 76%
“…However, the contribution of B o is minor due to small residual saturation and the change in IFT is more important since the recovery curve has a sharp increase. Bardon and Langeron (1980) also found a decreasing residual oil saturation using C 1 -C 7 mixtures at high pressures when measuring gas oil relative permeability.…”
Section: Resultsmentioning
confidence: 73%